THE PUBLIC POLICY (ORDRE PUBLIC) RULE OF THE EU SUCCESSION REGULATION AND THE HUNGARIAN INHERITANCE LAW (EU and comparative law issues and challenges series (ECLIC), 2019)
The EU Succession Regulation declares in Article 35 that “[t]he application of a provision of the law of any State specified by this Regulation may be refused only if such application is manifestly incompatible with the public policy (ordre public) of the forum”. This paper aims at analysing on the one hand the public policy (ordre public) rule of the EU Succession Regulation and on the other hand the Hungarian inheritance law with regard to the application of Article 35.